Effect of Prebiotic in Commercial Feed on the Growth of Catfish (Pangasius sp.) - Ida Hadijah (Jurnal Perikanan dan Kelautan, 2015)
A prebiotic is a non-digestible food ingredient that beneﬁcially aﬀects the host by selectively stimulating the growth or the activity of one or a limited number of bacteria in the colon. This research aimed to determine the effect of commercial feed containing prebiotics on the growth of catfish (Pangasius sp.). The experiment were done with four treatments and three replicates, namely control A (0% prebiotic), B (1% prebiotic), C (2% prebiotic), D (3% prebiotic). The treatment with the addition of 1% prebiotic can improve number of bacteria populations, protein retention, protein efficiency ratio, specific growth rates, feed efficiency and survival rate higher than the other treatments with the value of each  9.25 ± 0.09b%, 15.65 ± 3.83b%, 112.68 ± 25.22b%, 1.52 ± 0.16c%, 31.55 ± 5.1b% and 93.33 ± 6.67%.. Therefore, the addition of 1% prebiotic can promote the growth performance of catfish.